Selection of a Mutant of Escherichia coli Which Has High Mutation Rates - Helling, Robert B. (1968)
A mutation which causes high mutation rates in all other loci tested was induced with nitrosoguanidine and was selected through the ability of the progeny of such mutant cells to mutate to streptomycin resistance at a higher rate than the wild-type cells. This mutation (mut-2) and the Treffers' mutation (mutT1) mapped at approximately the same position to the right of leu. Specificity studies showed that the two mutations differ in rates of mutation produced.